2020
DOI: 10.1088/2053-1591/ab8655
|View full text |Cite
|
Sign up to set email alerts
|

Linear correlation between the c-axis lattice constant and superconducting critical temperature in FeSe0.5Te0.5 thin films

Abstract: Using x-ray diffraction, scanning electron microscopy, transmission electron microscopy, and electrical resistance analyses, we investigate structural and superconducting properties of FeSe 0.5 Te 0.5 films deposited by pulsed laser deposition on TiO 2 -buffered (CeO 2 -buffered) SrTiO 3 substrates with the buffer film thickness varying from 0 to several tens of nanometers. It is found that the SrTiO 3 /TiO 2 (or CeO 2 )/FeSe 0.5 Te 0.5 film in a proper thickness range of the buffer film shows a higher superco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…1 , only Fe y Se 1− x Te x and TiO 2 peaks are observed along the c -axis (00 l ), which indicates the Fe y Se 1− x Te x films to be the single tetragonal phase. Our previous work confirmed that TiO 2 as a buffer layer could increase the lattice match between Fe(Se, Te) film and STO substrate, so as to enhance the superconducting property of Fe(Se, Te) film 24 . We find that with increasing Te doping, the (00 l ) peaks significantly shift to a low angle.…”
Section: Resultssupporting
confidence: 72%
“…1 , only Fe y Se 1− x Te x and TiO 2 peaks are observed along the c -axis (00 l ), which indicates the Fe y Se 1− x Te x films to be the single tetragonal phase. Our previous work confirmed that TiO 2 as a buffer layer could increase the lattice match between Fe(Se, Te) film and STO substrate, so as to enhance the superconducting property of Fe(Se, Te) film 24 . We find that with increasing Te doping, the (00 l ) peaks significantly shift to a low angle.…”
Section: Resultssupporting
confidence: 72%
“…1, only FeySe1-xTex and TiO2 peaks are observed along the c-axis (00l), which indicates the FeySe1-xTex epitaxial films to be single tetragonal phase. Our previous work confirmed that TiO2 as a buffer layer could increase the lattice match between Fe(Se, Te) film and STO substrate, so as to enhance the superconducting property of Fe(Se, Te) film [23].…”
supporting
confidence: 71%
“…As a result, the in-plane and out-of-plane lattice constant are closely related, and the c-axis lattice constant of the FST film changes depending on the lattice mismatch of the interface between FST and TiO 2 -buffered substrate. Since the in-plane lattice constant of TiO 2 is between those of FST and the substrates, the interface between FST and TiO 2 -buffered substrate has smaller lattice mismatch and smaller strain, which is conductive to the superconductivity of the FST [18]. The crystal quality and atom distribution between the interface of FST/TiO 2 heterostructure will be further analyzed by STEM images.…”
Section: Resultsmentioning
confidence: 99%